(Kearifan Lokal Dalam Pengelolaan Keanekaragaman Tumbuhan Di Hutan Adat Temedak Di Desa Keluru Kecamatan Keliling Danau Kabupaten Kerinci) - Dharma Ferry; Seprianto Seprianto; Rodi Hartono; Heri Mudra; Hermairi Hermairi (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2017)
This research was conducted based on local wisdom in Keluru. The society has awarness to keep Temedak Customary Forest of Keluru. They understand the positive effects of that Customary Forest. This Forest was decided as the Customary Forest in written form since 1927. That Customary Forest has many diversities of flora. Then, there are many rules which have made to keep the conservation of that forest in both customary law and the policy of local and village government. The rule is related to the prohibition of Customary Forest exploitation. The purpose of this research is to know how the management of flora diversities in Temedak Customary Forest of Keluru. The data and information were obtained from field observation of the customary forest condition and interview with some informants. The informants consisted of the customary functionary, village government, and society. The data were analyzed by qualitative method. The result of this research showed that the management of flora diversity in Temedak Customary Forest of Keluru have been done well. Local wisedom such as the customary rules have been implemented well. This research describes about the local wisdom of society in keeping and managing conservation of customary forest.